Thao Vy Mac COVID-19 Pandemic Slideshow - Mac, Thao Vy::::::::: (2021)
A slideshow of photographs reflecting Thao Vy Mac's personal experiences with the COVID-19 pandemic. Images include empty store shelves, social distancing guides, homemade masks, and plastic barriers at the bank.